2015
DOI: 10.1039/c4ra13606c
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical property vs. medium: mononuclear, dinuclear and trinuclear Zn(ii) complexes

Abstract: Mononuclear, acetato bridged dinuclear and phenoxo bridged trinuclear Zn(ii) complexes have been synthesized. Their photophysical properties were characterized spectroscopically and with TDDFT and attributed to intra ligand (π → π*) charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 65 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…18 Zn(II) is one such example, and there are only a few reports on Zn(II) complexes exhibiting multiple nuclearities prepared from a series of similar ligands. 4,8,9 A fingerprint is a unique identification feature of a human being, and it constitutes valuable evidence in crime scenes. However, in most cases, the fingerprints are latent to the naked eyes and require development techniques for visualization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Zn(II) is one such example, and there are only a few reports on Zn(II) complexes exhibiting multiple nuclearities prepared from a series of similar ligands. 4,8,9 A fingerprint is a unique identification feature of a human being, and it constitutes valuable evidence in crime scenes. However, in most cases, the fingerprints are latent to the naked eyes and require development techniques for visualization.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control the nuclearity of complexes derived from a series of similar ligands is important in developing metal–organic systems with predesigned properties. However, such nuclearity control is often difficult due to the involvement of multiple variables. The common approaches employed for nuclearity control in metal complexes include changing the anions, reaction temperatures, reaction conditions, and additives. Similarly, the development of strategies for the interconversion of metal complexes of different nuclearities is also vital as a synthetic approach. Still, the predictable nuclearity control and the interconversion of metal complexes of different nuclearities remain challenging tasks to achieve. Further, the situation becomes more complicated if the metal ions do not show any crystal field stabilization energy for a particular geometry .…”
Section: Introductionmentioning
confidence: 99%
“…The coordination environment of the title compound, illustrated in Fig. 1, has been observed in zinc(II) complexes with tridentate N,N,O ligands (Hens & Rajak, 2015;Kim et al, 2015). Transition metal complexes of the related tridentate ligand, 1,3(2-pyridyliminomethyl)phenylenediamine, have been shown to form a variety of interesting complex structures (Kundu et al, 2015;Kumar et al, 2011;Bluhm et al, 2003;Souza et al, 2011;Sanyal et al, 2014;Okeke et al, 2017a,b;Okeke et al, 2018).…”
Section: Chemical Contextmentioning
confidence: 99%
“…This phenomenon suggested that Cd 2+ is quickly bound with PMPA. 46 The interesting revelations in the UV-visible spectral studies with various metal ions motivated us to further investigate detailed fluorescence spectroscopic studies. Addition of metal ions changed the emission spectrum of PMPA to different extents.…”
Section: Response Of Pmpa Toward CD 2+ Ionsmentioning
confidence: 99%